UPAYA PENINGKATAN KOMPETENSI PROFESIONAL GURU PKN DI SMA NEGERI 1 ENAM LINGKUNG KABUPATEN PADANG PARIAMAN - Arisman Sabir; Muhammad Hakiki (Program Studi Teknologi Informasi, Universitas Muhammadiyah Muara Bungo, 2020)
Abstract —This research of background with observation early which is writer do/conduct in field, writer see various problem that happened in course of study of class like less maximal it him learn the the PKN in teaching. This matter seen moment the happening of study process take place. Pursuant to background of writer interest to check about